Sorghum pericarp pigments are associated with the contents of carotenoids and provitamin A - Shen, Yanting (Kansas State University, 2016)
Sorghum is a staple crop consumed in certain regions of Africa and Asia, where vitamin A deficiency is prevalent. However, the correlation of sorghum intake and vitamin A deficiency is inconsistent. The objective of this study was to identify and quantify the carotenoids and pro-vitamin A in the selected sorghum accessions with various pericarp pigments by using LC-MS. Among of total five carotenoids (α-carotene, β-carotene, lutein, zeaxanthin, and β-cryptoxanthin) that were identified and quantitated, three (α-carotene, β-carotene and β-cryptoxanthin) are precursors of vitamin A. The highest content of total carotenoids was detected in the sorghum accessions with yellow pericarp (PI656096, PI585374, PI563448, PI585351), while the highest β-carotene content was found in the accessions with brown or yellow pericarp (PI655996, PI656096, PI585374, PI563448, PI585351). The lowest carotenoids were found in the accessions with white pericarp (PI533943, PI656112, PI565121, PI560493). The pro-vitamin A was 584.9 ± 38.9 ng/g DW in yellow pericarp, 250.6 ± 28.9 ng/g DW in brown pericarp, and 89.0 ± 12.3 ng/g DW in white pericarp, respectively. It appeared the phenotypic diversity of sorghum pericarp colors was strongly associated with the contents of carotenoids and pro-vitamin A, indicating a different impact of various sorghum varieties on vitamin A deficiency and suggesting a possible prevention of vitamin A deficiency by breeding certain sorghum varieties with pericarp pigments.
Keywords: Sorghum; Vitamin A deficiency; Pericarp pigment; Pro-vitamin A; Carotenoid